Turkish democracy: a model for the Arab World - Kayadibi, Saim; Birekul, Mehmet (International Islamic University Malaysia, 2011)
In retrospect, the ‘Arab Spring’ has brought dramatic and significant social changes in many countries in the Middle East. In stark contrast to the Arab uprisings, the changes and transformation that have taken place in the political landscape in Turkey were more peaceful and less damaging to the society. Taking into account of the two scenarios, warrants for a diagnostic investigation to identify the underlying reasons as to why the Turkish transformation happened peacefully, without any bloodshed, compared to the Arab world. The resistance movement in the Arab world was prepared to take the democratic and secular state of Turkey as a model in their demand for a change in their own countries. The people in the Arab world also witnessed the overwhelming support enjoyed by the conservatives of the AK Party (Justice and Development Party) led by Recep Tayyip Erdoğan. Very precisely, this paper intends to scrutinize the role of Turkey in giving the inspiration for the Arab uprising, analyze the declaration of the leaders and the people’s opinions stated in the print and electronic media with regards to the uprising. The overall analysis of this paper will make inferences to Turkey as an exemplary democratic country for the Arab world.